Infecção congênita pelo citomegalovírus: estudo realizado na Fundação Santa Casa de Misericórdia do Pará - WEIRICH, Judith (1997)
Cytomegalovirus (CMV) is a DNA virus classified in the Hespesviridae family and Betaherpesvirinae subfamily. It has a worlwide distribution and may cause congenital and perinatal infection, as well acquired infection in children and adults. CMV has been associated with high rates of morbidity and mortality among immune deficient or immune suppressed patients. This investigation was carried out from November 1994 to May 1995 in the maternity of a local public hospital - ''Fundação Santa Casa de Misericórdia do Pará"- and the main objective was to assess the incidence of congenital CMV infection among neonates in Belem, Brazil. We enrolled 663 newborns and their mothers to participate in our study. The weights of neonates ranged from 900 to 5450 g (mean of 3046 g) and low birth weights were recorded in 11,4% of them. For diagnostic purposes, clinical specimens (spittle) were inoculated on to culture cell lines prepared from human foreskin fibroblasts, yielding virus isolation in 21 (3,2%) of patients. Cord blood samples have been tested for the presence of CMV -specific IgM by using ELISA, with positive results in 14 (2,1%) patients. Differences of sensitivities between these methods were analysed by using the McNemar' test (Comparing proportions in paired groups) and the X2 test of homogeneity, as appropriate. Virus isolation proved to be more sensitive than serology, with p values of 0,0233 and less than 0,01 for the former and latter statistical tests, respectively. Six (28,5%) among the 21 infected neonates were shown to be congenitally infected, presenting with typical signs and symptoms suchs as: microcephaly (4), prematurity (3), hepatosplenomegaly (2), low birth weight (2) and jaundice (1). Sera from mothers were also tested for the presence of CMV-antibody by ELISA The detection of specific IgG was recorded in 90,2% of them, whereas IgM seropositivity was detected in 4 (19,0%) of those 21 mothers of infected children. Data gathered during routine interviews with mothers revealed low social economical leve1 and indicated that 26,4% of them had no prenatal medical assistance. Their ages ranged fiom 12 to 42 years (mean age of 22,2) and all mothers of CMV-infected children were aged less than 25 years.